2015
DOI: 10.1007/jhep10(2015)074
|View full text |Cite
|
Sign up to set email alerts
|

Interference effects for H → W W → ℓ ν q q ¯ ′ $$ H\to W\;W\to \ell \nu q{\overline{q}}^{\prime } $$ and H → Z Z → ℓ ℓ ¯ q q ¯ $$ H\to ZZ\to \ell \overline{\ell}q\overline{q} $$ searches in gluon fusion at the LHC

Abstract: Signal-background interference effects are studied for H → W W and H → ZZ searches in gluon fusion at the LHC. More specifically, the interference in the channels with semileptonic weak boson pair decay is analysed for light and heavy Higgs masses with minimal and realistic experimental selection cuts. In the semileptonic decay modes, the interference is affected by tree-level background contributions enhanced by 1/e 2 relative to the gluon-fusion continuum background in the fully leptonic decay modes. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…[26], which were calculated using a previous version of gg2VV with a different phase space implementation based on a decomposition into sections. Furthermore, results for similar processes calculated using the same code show excellent agreement with a fully independent implementation [79].…”
Section: Calculational Detailsmentioning
confidence: 53%
“…[26], which were calculated using a previous version of gg2VV with a different phase space implementation based on a decomposition into sections. Furthermore, results for similar processes calculated using the same code show excellent agreement with a fully independent implementation [79].…”
Section: Calculational Detailsmentioning
confidence: 53%
“…ZZ+jet production was computed at NLO QCD [27]. The loop-induced gg → ZZ + X subprocess, which provides a separately finite O(α 2 S ) contribution, is known at leading order (LO) [28][29][30][31][32][33][34][35][36][37] and was recently computed at NLO considering only gg-initiated partonic channels [38][39][40], using the two-loop helicity amplitudes for gg → V V of Refs. [41,42].…”
mentioning
confidence: 99%
“…[62], for which results are not yet available. We believe this tree-2-loop contribution is small compared to the 1-loop-1-loop contribution we compute, because tree-1-loop interference was found to be small compared to 1-loop-1-loop interference in similar processes [67,92], but the non-factorisable contribution may be enhanced due to the lifted colour singlet final state restriction. 13 In the inclusive case, nonfactorisable corrections are suppressed by Γt/mt, i.e.…”
Section: Resultsmentioning
confidence: 55%
“…(3.5), since our study focuses on the region with 2m t < M tt < M h 2 , the double pole approximation [91] with a pair of on-shell top quark states -shown in red in figure 3 -is applied to simplify our calculations. It has been shown that higher-order corrections to interference can be larger than the interference at LO [66,67]. In the case where LO involves treelevel amplitudes, this can be understood as follows: the relative phase that induces large interference arises primarily through the absorptive part of loop graphs.…”
Section: Calculational Detailsmentioning
confidence: 99%
See 1 more Smart Citation